La contribución de Antonio Sáez Espligares a la Arqueología prehistórica de San Fernando en los años 90 del siglo XX. Testimonios de una fructífera colaboración - Ramos Muñoz, José Francisco (Revista Atlántica-Mediterránea de Prehistoria y Arqueología Social, 2021)
The collaboration estimates of the author with the honoree in this issue of the Magazine, Antonio Sáez Espligares, in works carried out in San Fernando (Cádiz) in the 90s of the last century are presented.